Iranian nurses' perception of the public image of nursing and its association with their quality of working life - Fariborz Roshangar; Amin Soheil; Golshan Moghbeli; Taneal Wiseman; Hossein Feizollahzadeh; Neda Gilani (Wiley, 2021)
Abstract Aim To investigate the association between the nurses' perception of the public image (PI) of nursing and the quality of nursing work life (QNWL). Design A descriptive correlational study. Methods 250 nurses of 12 hospitals affiliated with Tabriz University of Medical Sciences were sampled using a proportionate stratified sampling technique. Porter Nursing Image Scale and Brooks QNWL Scale were used for collecting data. Results There was a significant positive correlation between nurses' perception of their public image and QNWL (r = .158, p = .012). Nurses' perception of their PI along with other significant predictors including gender, age, position, work shifts, residency, financial status, level of family support, spouse's education and spouse's job significantly explained 15.2% of the predictability of QNWL (F(10,175) = 3.017, p = .001). Findings imply that enhancement of nurses' psychological status (nurses' perception of the public image of their profession) may improve their functional status (quality of nursing work life).